Handicraft Production and Employment in Indian: An Economic Analysis (Global Journal of Human-Social Science, 2014)
Country like India, where tradition, rituals and culture still hold a significant value and importance, crafts have been able to retain its essential matter in the form of many definitions, according to individuals, groups and organisations. Handicrafts commonly refer to hand-made artisan crafts or artisanry. Skilled people create different kinds of items starting from consumer goods to pretty pieces out of paper, wood, clay, shells, rock, stone, metal etc. with the help of simple tools. These kinds of items are called handicrafts owing to the fact that these crafted items are exclusively hand-made without the usage of any machine.
Keywords: crafts; handicrafts; hand-made; different kinds